2004
DOI: 10.1016/j.fcr.2004.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Utility of indirect and direct selection traits for improving Striga resistance in two sorghum recombinant inbred populations

Abstract: Breeding of sorghum (Sorghum bicolor L. Moench) for resistance to the parasitic weed Striga hermonthica (Del.) Benth. has been hampered by the difficulty of evaluating host resistance in the field and lack of reliable screening techniques. Therefore, we investigated the value of various indirect and direct measures of Striga resistance as selection traits. Two sorghum recombinant inbred populations of 226 F 3:5 lines each were developed from the crosses (1) IS 9830 Â E 36-1 and (2) N 13 Â E 36-1. Strigaresista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 21 publications
6
35
0
Order By: Relevance
“…The same observation was made on the resistance mechanism of some cereal cultivars in Striga controlling (Kuiper et al, 1998). The existence of differences in cultivar susceptibility against Striga hermonthica has been highlighted among sorghum cultivars (Omanya et al, 2004;Rodenburg et al, 2006) and maize (Zea mays L.) cultivars (Kim et al, 1998). Our results confirmed that of Hariri (1990) and Dibong et al (2009) from their experiments on artificial infestations with other species of Loranthaceae.…”
Section: Discussionsupporting
confidence: 81%
“…The same observation was made on the resistance mechanism of some cereal cultivars in Striga controlling (Kuiper et al, 1998). The existence of differences in cultivar susceptibility against Striga hermonthica has been highlighted among sorghum cultivars (Omanya et al, 2004;Rodenburg et al, 2006) and maize (Zea mays L.) cultivars (Kim et al, 1998). Our results confirmed that of Hariri (1990) and Dibong et al (2009) from their experiments on artificial infestations with other species of Loranthaceae.…”
Section: Discussionsupporting
confidence: 81%
“…Many different selection measures have been developed for resistance. All of these measures are based on the number of aboveground Striga plants and vary from a single count at a specific moment in time (Adetimirin et al, 2000a;Omanya et al, 2004) or the maximum number of aboveground Striga plants (Wilson et al, 2000(Wilson et al, , 2004Rodenburg et al, 2005) to the area under the Striga number progress curve (ASNPC) (Adetimirin et al, 2000a;Haussmann et al, 2000;Wilson et al, 2000Wilson et al, , 2004Omanya et al, 2004;Rodenburg et al, 2005). Complete resistance, also referred to as immunity against Striga, has not yet been found.…”
Section: Introductionmentioning
confidence: 99%
“…Where a potential host plant defense is expressed, it can be narrowed to a specific stage in the parasite life cycle. This has been made possible through the development and extensive exploitation of advanced laboratory-based bioassays, which have provided weed researchers with fine phenotyping tools Ejeta, 2007;Omanya et al 2004). Based on the knowledge gained, it has been suggested that the overall expression of resistance to the parasites can be broken down into two major parts, pre-attachment and post-attachment, in the establishment of the parasitic association.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…Research effort invested to characterize the mechanisms behind and inheritance of resistance to Striga has been followed by the development of molecular markers. Recently, mapping of chromosomal regions affecting qualitative or quantitative traits has received growing attention in millets Ejeta and Butler, 1993;Haussmann et al, 2001a;Omanya et al, 2004;Rich et al, 2004;Mohamed et al, 2003;Kountche, 2013;Moumouni et al, 2015). In sorghum, several populations segregating for genes associated with low germination stimulant production (lgs), low haustorial initiation, mechanical barriers, hypersensitive response, and incompatible response mechanisms of Striga resistance have been developed using the source materials (Ejeta et al, 2000;Haussmann et al, 2000;Grenier et al, 2001Grenier et al, , 2007Rodenburg et al, 2006;Omanya et al, 2004;Mutengwa et al, 2005).…”
Section: Marker-assisted Selectionmentioning
confidence: 99%
See 1 more Smart Citation